A Nationwide Evaluation of Antibiotic Consumption in Kazakhstan from 2019 to 2023 - Yuliya Semenova; Ademi Yergaliyeva; Ainur Aimurziyeva; Almira Manatova; Anargul Kuntuganova; Larissa Makalkina; Nurgul Aldiyarova; Daniil Semenov; Lisa Lim (Antibiotics)
Background/Objectives: There has been a lack of a holistic approach to evaluating antibiotic consumption in Kazakhstan over the past few years using an internationally recognized methodology. Therefore, this study aimed to provide a nationwide evaluation of antibiotic consumption in Kazakhstan during the period 2019–2023. Methods: Defined daily doses per 1000 inhabitants per day (DIDs) were calculated for systemic antibiotics (J01 code of the Anatomical Therapeutic Chemical Classification System (ATC)) following the methodology established by the Global Antimicrobial Resistance and Use Surveillance System (GLASS-AMC). The average annual percent change (AAPC) was computed for each chemical agent, pharmacological group, and J01 in general to evaluate past trends in antibiotic consumption. Results: The consumption of J01 antibiotics ranged between 10.869 DIDs (2022) and 14.470 DIDs (2020). There was an increase in antibiotic consumption during 2020 and 2021, but the overall trend was declining, with an AAPC of −2.45%. Azithromycin was the most consumed systemic antibiotic, followed by ceftriaxone and ciprofloxacin. The consumption of “Watch” group antibiotics prevailed in Kazakhstan during the study period, with the number of people consuming the top five “Watch” group antibiotics rising from 72,578 in 2019 to 94,617 in 2023. Conclusions: The findings of this study are crucial for the reorganization of the national antimicrobial stewardship program.